Diversity and emendation of the genus Planktoniella (Bacillariophyceae), with descriptions of P. tubulata sp. nov. and P. trifurcata sp. nov. Issue 5 (24th May 2021) - Yue, Fang; Niu, Biaobiao; Guo, Yaqiong; Lundholm, Nina; Li, Yang
Abstract : For the first time, LSU and SSU sequences were obtained from four species of the marine planktonic diatom Planktoniella . Samples were collected and cultured from Chinese coastal waters, and morphological observations were made using light and scanning electron microscopy. Combined morphological and DNA sequence data revealed two new species herein described as Planktoniella tubulata and Planktoniella trifurcata . Planktoniella tubulata is characterized by the prominent external tubes of two rimoportulae and the long external tubes of the marginal fultoportulae. The latter are organized regularly in a ring, externally on the mantle, and protrude parallel to the valvar plane. Planktoniella trifurcata is unique in having mucilaginous extensions that usually expand into three lobes, and external extensions of the marginal fultoportulae being either tubes or spines. In the phylogenetic analyses inferred from SSU and LSU sequences, the four analyzed Planktoniella taxa formed a well‐supported monophyletic group. A suite of three characters, mucilage membranes or wings, two marginal rimoportulae, and mantle ribs are diagnostic for Planktoniella . Based on these detailed ultrastructural observations, the description of Planktoniella is emended.